Existence of capital at the commencement of joint ventures: an analysis of the Shari‘ah position in the context of modern money and banking practices - Sadique, Muhammad Abdurrahman (International Islamic University, 2009)

(untitled)
The objective of this study is to verify the Shari'ah position on the existence of capital in joint ventures based on musharakah and mudarabah, and its relevance and implications in the context of joint ventures formed between Islamic banks and clients in the course of financing on equity basis, especially in view of changes that have taken place in the nature and identity of money. The position of Islamic schools of law on the issue is ascertained from major works of Islamic law, and the implications of the Shari'ah requirement examined. The current practice of Islamic banks and the contemporary Shari'ah approaches to the issue are scrutinized; and the change in the nature and identity of money is analyzed to determine whether it is significant in this regard. According to the texts of Islamic law, a joint venture involving monetary capital could be set in motion on the basis of capital that is existent and present, with clear agreement regarding the share of each partner. While gradual release of capital is admissible, prior existence of capital is necessary. Due to credit supplementing real money in a substantial manner, the identity of money in the current fiscal environment appears to have undergone significant change, the nature and influence of which need to be reassessed through a separate study. This is crucial for determining the form in which the existence and presence of capital could be ensured. The emphasis placed in the Shari'ah on existence and presence of capital could indicate a measure for thwarting unwelcome monetary expansion, thus controlling inflation. This study only attempts to verify the Shari'ah position on existence of capital in the context of joint ventures financed by Islamic banks, based on their current practice. Broader research and academic effort is needed to assess the impact of the changed nature of money on related Shari'ah rulings.